2020
DOI: 10.3390/gidisord2030025
|View full text |Cite
|
Sign up to set email alerts
|

VEGF Expression in Colorectal Cancer Metastatic Lymph Nodes: Clinicopathological Correlation and Prognostic Significance

Abstract: Background: Angiogenesis plays an important role in colorectal cancer (CRC) tumorigenesis and metastatic progression. Methods: The present series consisted of CRC lymph node metastasis (LNM) tissue samples from 210 patients. Archival paraffin embedded LNM tissue were used to build up tissue microarray blocks and VEGF expression was immunohistochemically assessed. Results: VEGF-A and VEGF-C are overexpressed in LNM. VEGF-A was associated with patient age (p < 0.001), and VEGFR-2 and VEGFR-3 with CRC relapse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…As an essential angiogenic regulator, VEGF contributes to cancer genesis and development, but is also a vital therapeutic target ( 37 ). It has been suggested that up-regulation of VEGF is associated with advanced cancer stages, particularly lymph node metastasis and angiolymphatic invasion, and it may also predict a poor prognosis for CRC ( 38 , 39 ).Taken together, serum based miR-1539 may provide clues underpinning molecular mechanisms for discrepant CRC prognoses (RCRC versus LCRC), and targeted anti-VEGF therapy. However, further studies are required to verify these observations.…”
Section: Discussionmentioning
confidence: 99%
“…As an essential angiogenic regulator, VEGF contributes to cancer genesis and development, but is also a vital therapeutic target ( 37 ). It has been suggested that up-regulation of VEGF is associated with advanced cancer stages, particularly lymph node metastasis and angiolymphatic invasion, and it may also predict a poor prognosis for CRC ( 38 , 39 ).Taken together, serum based miR-1539 may provide clues underpinning molecular mechanisms for discrepant CRC prognoses (RCRC versus LCRC), and targeted anti-VEGF therapy. However, further studies are required to verify these observations.…”
Section: Discussionmentioning
confidence: 99%
“…In most papers, exposure to T3s caused downregulation of VEGFA in the CRC cells. Furthermore, in a clinical study involving lymph node metastasis (LNM) from patients with CRC, there was elevated expression of the VEGF family, especially of VEGFA in LNM, which was associated with the patients' age (p-value < 0.001) [55]. Interestingly, high expression of VEGFA in the primary tumor was positively associated with other ligands and receptors with regards to LNM, implying a mutual effect.…”
mentioning
confidence: 99%
“…Reduced RELA expression, resulting in deceased activation of the NF-κB signaling pathway, which inhibited carcinogenesis [52,53] Cancer progression CCND1 ()  CCND1 gene was detected in tumors from about 50% (54 out of 111) of CRC patients; absent in normal mucosa [54] VEGFA ()  Elevated expression of the VEGF family, especially of VEGFA, was reported in CRC patients with LNM [55] CTNNB1 ()  CTNNB1 codes for ꞵ-catenin, which supports tumor growth  A significant link between mutations in CTNNB1 gene and MSI [56]  Downregulat.ed;  Upregulated; CB: candidate biomarkers; CRC: colorectal carcinoma; LNM: lymph node metastasis; MSI: microsatellite instability; T3s: tocotrienols. Italics refer to the gene name of the protein.…”
mentioning
confidence: 99%
See 2 more Smart Citations